2010
DOI: 10.1167/iovs.09-4159
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Glial (Müller) Cells: Sensing and Responding to Tissue Stretch

Abstract: A novel technique was developed for real-time monitoring of Müller cells during retinal stretch, which allowed the identification of Müller cells as a mechanoresponsive cell type. Mechanical stress triggers molecular responses in Müller cells that could prevent retinal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 71 publications
5
98
0
3
Order By: Relevance
“…After partial detachment of the vitreous from the retina, vitreous fibers adhering to Müller cells at sites of vitreoretinal attachment exert tractional forces onto the cells; this activates the cells and results in cellular hypertrophy and proliferation as well as vascular leakage [85]. Mechanical stress induces calcium responses (likely induced by stretch-activated calcium-permeable cation channels [86]), activation of ERK1/2, and upregulation of the transcription factor c-Fos and of bFGF in Müller cells [87]. Mechanically stressed Müller cells release growth factors (e.g.…”
Section: Epiretinal Membrane Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…After partial detachment of the vitreous from the retina, vitreous fibers adhering to Müller cells at sites of vitreoretinal attachment exert tractional forces onto the cells; this activates the cells and results in cellular hypertrophy and proliferation as well as vascular leakage [85]. Mechanical stress induces calcium responses (likely induced by stretch-activated calcium-permeable cation channels [86]), activation of ERK1/2, and upregulation of the transcription factor c-Fos and of bFGF in Müller cells [87]. Mechanically stressed Müller cells release growth factors (e.g.…”
Section: Epiretinal Membrane Formationmentioning
confidence: 99%
“…Mechanically stressed Müller cells release growth factors (e.g. bFGF) and adenosine 5′-triphosphate (ATP) [87,88,89]. Calcium influx [through stretch-activated and voltage-gated calcium channels, and ionotropic purinergic (P2X 7 ) receptor channels] and subsequent activation of calcium-activated big-conductance potassium (BK) channels are required for growth factor- and ATP-induced proliferation of Müller cells [90,91,92,93,94].…”
Section: Epiretinal Membrane Formationmentioning
confidence: 99%
“…Two predominant approaches have been utilized to apply experimental forces to neurons. In the first approach, forces are applied to the entire neuron (Lu, Franze et al 2006;Chetta, Kye et al 2010;Lindqvist, Liu et al 2010). In the second approach, forces are applied directly to the axon by pulling on the growth cone.…”
Section: Overview Of the Axon Stretch Growth Bioreactor Systemmentioning
confidence: 99%
“…It has also been suggested that these cells are able to regulate the biomechanical properties of the retina through changes in the expression of cytoskeletal intermediary filaments, such as GFAP and vimentin [28][29][30]. Müller cells have been found to express mechanosensory Ca 2+ ion channels [2,[31][32][33] which respond to changes in cell membrane tensility by Ca 2+ influx [31,35].…”
Section: The Role Of Müller Cellsmentioning
confidence: 99%